Implementasi Model Project Based Learning (PjBL) untuk Meningkatkan Hasil Belajar IPAS pada Materi Transformasi Energi Siswa Kelas IV Sekolah Dasar - Laily Novitasari; Goffar Ar Rozzaq; Komarudin; Eva Septiana Dewi; Irfani Amrina Rosyada; M Fadlullah Zainal Abidin; Arif Mahya Fanny; Lely Nugraheni (Universitas Muhammadiyah Magelang, 2026)
This study aims to describe the implementation of the Project Based Learning (PjBL) model and analyze the improvement of science learning outcomes on energy transformation material among fourth-grade students at SDN Sumur Welut III/440. The research method used was Classroom Action Research (CAR) with the Kemmis and McTaggart design model, conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection phases. The research subjects were 29 fourth-grade students. Data collection techniques included learning outcome tests, observation, and documentation. Data analysis was conducted descriptively using both qualitative and quantitative approaches. The results showed a significant improvement in learning completeness: from an initial 45%, increasing to 62% in Cycle I, and reaching 90% in Cycle II. The class average score also improved from 72 in Cycle I to 85 in Cycle II. Therefore, the implementation of the PjBL model proved effective in improving IPAS learning outcomes on energy transformation material in elementary school.